Haemorrhage and Other Complications in Pregnant Women on Anticoagulation for Mechanical Heart Valves; a Prospective Observational Cohort Study - Kariv, Sarah (Department of Medicine, 2020)
Objective: To document maternal and foetal morbidity and mortality in anticoagulated, pregnant patients with mechanical heart valves until 42 days postpartum. Methods: In a tertiary single-centre, prospective cohort, 178 consecutive patients at the cardiac-obstetric clinic were screened for warfarin use between 1 July 2010 and 31 December 2015. Of 33 pregnancies identified, 29 were included. Patients received intravenous unfractionated heparin from six to 12 weeks’ gestation and peripartum, and warfarin from 12 to 36 weeks. Maternal outcomes including death, major haemorrhage and thrombosis, and foetal outcomes were documented. Results: There were two maternal deaths, five returns to theatre post-delivery, eight patients transfused, six major haemorrhages, one case of infective endocarditis and three ischaemic strokes. Ten pregnancies had poor foetal outcomes (six miscarriages, three terminations, one early neonatal death). Twenty patients required more than 30 days’ hospitalisation, and 15 required three or more admissions. HIV positivity was associated with surgical delivery (p = 0.0017). Conclusions: Complication rates were high despite centralized care.